If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7+4x/3-12=-3
We move all terms to the left:
7+4x/3-12-(-3)=0
We add all the numbers together, and all the variables
4x/3-2=0
We multiply all the terms by the denominator
4x-2*3=0
We add all the numbers together, and all the variables
4x-6=0
We move all terms containing x to the left, all other terms to the right
4x=6
x=6/4
x=1+1/2
| 6x-9=7×+7 | | 7x+7=10×-38 | | x-3=+3-x | | 16r+2r^2=54 | | 2(2y-1)=-10 | | (6-z)(3z-1)=0 | | e/15=15 | | 2x(7x+9)=90 | | 2r(9-r)+2r^2=54 | | 218=24*2+2w | | 0m+6=369 | | (7x-1)^1/3+11=7 | | 6x-14+24=46 | | 13x-11=7x+10 | | x^2+24x+30=0 | | 1 8y−2 3=51 2 | | 16^x+4=32^2x-10 | | 3x-10=5×-70 | | 3r+7=21 | | N-12x8=12 | | 48=12+b | | 64^2x+3=16^x+2 | | 3^6x+3=27^x+5 | | 3/4x+5=8 | | -7x+22+2x-14=12 | | 8(z-9)+11=-2z+8 | | 3x+5-2x=15-6 | | 6.98x+6.98=13.96 | | 2x+7=-3+2x | | 3^x2+x=9 | | 2(w+10)+1=6w-5 | | 8m+50=914 |